Developing computer software using Quranic script (Jawi) - Md Ghalib, Mohd. Feham (2013)
The presentation outlines the technical details of digitising/encoding Jawi scripts and how they can be used in the computer. Several fonts enabling the users to type Jawi scripts also being presented. The use of current mobile device also can be accommodated for writing Jawi scripts via several potential apps available on both IOS and android platforms. The presentation suggests some possible future research in this area particularly related to automatic natural language processing.